Calling a spade a spade. Russian propaganda rhetoric as probable evidence of genocidal intentions - Mykola Riabchuk (Політичні дослідження, 2023)
The number and scale of war crimes and crimes against humanity committed by the Russian military in Ukraine since the start of the all-out invasion in February 2022 have prompted many experts and politicians to define this brutality as genocide and seek prosecution of the perpetrators under international law.Ukrainian investigators and prosecutors, in cooperation with foreign colleagues, are carefully documenting relevant facts, while lawyers and diplomats are looking for optimal ways to administer justice within existing or newly created international judicial institutions. At the same time, many express a warning that among the four types of crimes recognized by the UN as the most serious and those that do not have a statute of limitations, the crime of genocide is the most difficult to prove in judicial practice, because the number of war crimes in itself, however brutal and large-scale, does not make them genocide from a legal point of view, if the most important and necessary for such a formal and legal qualification is not proven: genocidal intent on the part of the military and/or political leadership of the aggressor country. Politicians usually do not give such orders in writing, and even make them orally, as a rule, in a veiled form. Therefore, it is necessary to prove genocidal intentions in court on the basis of indirect evidence — an analysis of the entire sum of the statements of high-ranking officials of the aggressor country, who ideologically justify and encourage genocide, using various euphemisms at the same time (calling, for example, for the extermination of the fictional "Nazis" in Ukraine, under which they have meaning all self-conscious Ukrainians), as well as — on the basis of a comparison of veiled genocidal statements with the corresponding systematic actions of the occupying forces and the administration, which clearly translate the ideological instructions of the leadership into the practical plane.The author of the article shows that the genocidal intentions of the Kremlin, despite all their rhetorical veiling, can be proven if the corresponding anti-Ukrainian rhetoric of Russian government officials, experts and propagandists is systematically analyzed, deconstructed and contextualized as a certain integrity, in close connection with the specific actions of the occupying army and administration.